Responsibility Of Land Deed Officials (PPAT) Towards Disputes Between The Parties In Court Relating To Deeds They Have Made (Decision Study Number: 32/Pdt.G/2022/PN Pdg) - Aldila, Ridho (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2024)
This study aims to determine and analyze the position of PPAT regarding the deeds he made for the parties bound by the deed and the responsibility of PPAT towards disputes between the parties in court regarding the deeds he made (Decision Study Number: 32/Pdt.G/2022/Pn Pdg). The research approach method used in this thesis is the normative legal research method. The specification of this study is descriptive analysis. The type of data used in this study is primary data including 1)1945 Constitution; Civil Code;PP No. 37 of 1998 concerning the Regulation of the Position of Land Deed Making Officials; PP No. 24 of 2016 concerning Amendments to PP No. 37 of 1998 concerning the Regulation of the Position of Land Deed Making Officials and secondary and tertiary legal materials containing books and other supporting documents. Data collection for research with literature study The data analysis method used in analyzing the data is qualitative analysis. The results of the study show that the Position of PPAT regarding the deeds he made for the parties bound by the deed is that PPAT in carrying out his duties must be guided by a normative framework related to all actions to be taken to then be stated in the deed. The responsibility of PPAT for disputes between parties in court related to the deeds he made is divided into 3 (three) forms, namely:PPAT's civil, criminal and administrative responsibilities.